2008
DOI: 10.1136/bmj.a2428
|View full text |Cite
|
Sign up to set email alerts
|

Elbow extension test to rule out elbow fracture: multicentre, prospective validation and observational study of diagnostic accuracy in adults and children

Abstract: Objective To determine whether full elbow extension as assessed by the elbow extension test can be used in routine clinical practice to rule out bony injury in patients presenting with elbow injury. Design Adults: multicentre prospective interventional validation study in secondary care. Children: multicentre prospective observational study in secondary care. Setting Five emergency departments in southwest England. Participants 2127 adults and children presenting to the emergency department with acute elbow in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 16 publications
2
55
2
3
Order By: Relevance
“…However, the addition of point tenderness at the olecranon, epicondyles and radial head did not improve the sensitivity or specificity of the active ROM maneuvers in the detection of elbow fractures. [10][11][12] In our study, patients with partial limitation in one or two movements had no sign of fractures on the Xray. However, almost all patients with fracture had limited range in all movements.…”
Section: Discussionmentioning
confidence: 40%
See 4 more Smart Citations
“…However, the addition of point tenderness at the olecranon, epicondyles and radial head did not improve the sensitivity or specificity of the active ROM maneuvers in the detection of elbow fractures. [10][11][12] In our study, patients with partial limitation in one or two movements had no sign of fractures on the Xray. However, almost all patients with fracture had limited range in all movements.…”
Section: Discussionmentioning
confidence: 40%
“…Several studies have shown the sensitivity of elbow ROM in detecting fracture (92% in the study of Lamprakis et al, [13] 96.8% in the large study by Appelboam [12] and 100% in the study of Darracq [10] ).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations